Predictors of Recurrence in Symptomatic Large Artery Atherosclerosis and Cryptogenic Strokes—A Comparative Study. Issue 1 (June 2022) - Lotlikar, Radhika Sanjay; Saikiran, Karkala; George, Jithin; Namboodiri, Narayanan; Sylaja, P. N.; Sreedharan, Sapna Erat
Background and Purpose: Ischemic stroke has highest recurrence risk in the first-year, ranging from 5.7% to 14%, depending on etiology, with highest reported following cardioembolism and large artery atherosclerosis (LAA), while it is not negligible in cryptogenic strokes. We evaluated the utility of clinical, imaging parameters along with electrographic and echocardiographic biomarkers of atrial dysfunction in 2 etiological groups, namely LAA and cryptogenic strokes and compared the predictors of recurrence risk at 1 year. Methodology: All acute ischemic strokes admitted to Comprehensive Stroke Care Centre, Department of Neurology, Sree Chitra Tirunal Institute for Medical Sciences and Technology, Trivandrum, India for 1 year (July 2019 till June 2020) with 1 year completed follow-up were screened from electronic records. Strokes secondary to LAA and undetermined cause were compared for their clinical, imaging, and cardiac variables to predict risk of recurrence in the first year. Results: Of the 179 patients, 93 had strokes secondary to LAA and 86 had cryptogenic strokes (CS). Seventy-five patients had more than 1 event at presentation/follow-up. Recurrence risk did not differ between the 2 etiological subgroups at 1 year. Hypertension ( P = .016), multiple territory strokes ( P = .02), and dilated left ventricle (LA) chamber ( P = .047) were independently associated with recurrence risk in the entire cohort as well as within the undetermined group. Early hospitalization within 48 h reduced the overall recurrence risk ( P = .01), thus emphasizing the role of early etiological evaluation and initiation of secondary prevention in reducing future events, irrespective of etiology. Conclusion: In optimally managed LAA and cryptogenic strokes, presence of hypertension, multiterritorial infarcts, and dilated LA chambers increases the recurrence risk pointing to a likely cardiac substrate itself contributing to future stroke risk.